Rapid Microwave-Assisted Shape Controlled Synthesis of Silver Nanoparticles - Decato, Daniel A. (My University, 2012)
The majority of procedures for shape-controlled silver nanoparticle synthesis report the use of a common set of reagents: a source of silver ions, a reducing agent, a shape directing agent, and a capping/protective agent. Associated reaction times are long, typically ranging from 24-72 hours. The purpose of this study was to develop a rapid microwave-assisted synthesis that includes only water, silver ions, and polyvinylpyrrolidone (PVP), producing predictable sizes and shapes of silver nanoparticles in 20 minutes.
Color poster with text, diagrams, charts, images, graphs, and tables.
Keywords: Microwave spectroscopy; Microwave plasmas; Nanoparticles--Synthesis; Posters